Solvent-free synthesis, plasticization and compatibilization of cardanol grafted onto liquid isoprene rubber. (20th October 2021) - Wang, Peng; Liu, Jinling; Chi, Chongyi; Zhang, Yuxia; Chen, Denglong; Chen, Qinhui
Abstract: Liquid isoprene rubber (LIR) is commonly used as plasticizer in rubber processing industry. It shows poor compatibility with inorganic fillers. Herein, cardanol grafted onto LIR (CA- g -LIR) was synthesized by solvent-free method and used as the dispersed matrix of silica particles. Results show that the optimum reactive condition is that 7 phr of cardanol monomer and 0.2 wt % of 2, 2-Azobisisobutyronitrile (AIBN) initiator per 100 g LIR react for 12 h at 70 °C. At these conditions, grafting ratio is 6.01%. CA- g -LIR shows obvious plasticizing effect, as is certified by its far high elongation at break (increase of 800%), decreased viscosity (reduction of 62%) and glass transition temperature (Tg, decline of 5.0 °C) compared with LIR. Moreover, CA- g -LIR shows good interfacial performance. The dispersion of silica particles in CA- g -LIR is better than that in LIR. CA- g -LIR is obtained by a simple and green way, low-cost, easy for industrial production. It is expected to be acted as plasticizer and compatibilizer at the same time in rubber industry. Graphical abstract: Image 1 Highlights: Cardanol grafted onto liquid isoprene rubber obtained by solvent-free method. Increasing plasticizing effect originated from alkyl flexibility of cardanol. Interfacial action of SiO2 reinforced rubber increased by phenolic hydroxyl groups. Versatile CA- g -LIR is expected in industrial application by produced in batch.